Colorectal Cancer: Post-operative Complications and Their Risk Factors - Paužas, Henrikas; Akelaitytė, Raminta; Kriščiūnaitė, Ugnė (Lietuvos chirurgija, 2025)
Background. Colorectal cancer is one of the most common cancers in the world, and surgery remains the only curative treatment. However, post-operative complications impact patients’ outcomes and quality of life. Identifying risk factors for these complications is essential for improving surgical outcomes and patient safety. Methods. We conducted a retrospective study of 277 patients who underwent CRC surgery at the Hospital of Lithuanian University of Health Sciences Kauno Klinikos between January 1 and December 31, 2023. Data were collected on demographic, clinical, and surgical variables. Statistical analyses were performed using IBM SPSS software and included univariate and multivariate logistic regression to identify independent risk factors for postoperative complications. Results. The overall postoperative complication rate was 22.7%, with anastomotic leakage being the most common complication (8.2%). Logistic regression analysis identified older age as the only statistically significant independent risk factor for postoperative complications (p = 0.016). While urgent surgery and intra-operative complications showed strong associations with increased risk, these were not statistically significant in multivariate analysis. Conclusion. Our study highlights older age as a critical risk factor for postoperative complications in CRC surgery. Although the study is limited by its retrospective design and single-center sample, it provides valuable insights for improving patient outcomes.